Dental implant location via surface scanner: a pilot study - Miao Zhou; Hui Zhou; Shu-yi Li; Yuan-ming Geng (BMC, 2020)
Abstract Purpose Implant location is performed after placement to verify that the safety of neighboring anatomic structure and the realizability of prosthetic plan. Routine postoperative location is based on radiological scanning and raises the concerns on radiation exposure and inconveniency in practice. In the present study a location method based on surface scanning was introduced and the accuracy of this method was assessed in vitro. Material and methods A total of 40 implants were placed in 10 resin mandible models. The models were scanned with intraoral scanner (IS group) and extraoral scanner (ES group). The implant position was located with fusing the images of surface scanning and cone beam computerized tomography (CBCT) after implant placement. Deviations were measured between positions located by surface scanner and postoperative CBCT with the parameters: central deviation at apex (cda), central deviation at hex (cdh), horizontal deviation at apex (hda), horizontal deviation at hex (hdh), vertical deviation at apex (vda), vertical deviation at hex (vdh) and angular deviation (ad). Results In IS group, the mean value of cda, cdh, hda, hdh, vda, vdh and ad was 0.27 mm, 0.23 mm, 0.12 mm, 0.10 mm, 0.21 mm, 0.19 mm and 0.72°, respectively. In ES group, the mean value of cda, cdh, hda, hdh, vda, vdh and ad was 0.28 mm, 0.25 mm 0.14 mm, 0.11 mm, 0.22 mm, 0.20 mm and 0.68°, respectively. The implant deviations in IS and ES groups were of no significant difference for any of the measurements. Conclusions Dental implant can be located via surface scanner with acceptable accuracy for postoperative verification. Further clinical investigation is needed to assess the feasibility of the method.